A PER3 Polymorphism Interacts with Sleep Duration to Influence Transient Mood States in Women. (10th March 2016) - Viena, Tatiana D.; Gobin, Christina M.; Fins, Ana I.; Craddock, Travis J.A.; Tartar, Aurélien; Tartar, Jaime L.
Background: Expression of the clock family of genes in the suprachiasmatic nuclei (SCN) regulates the molecular control of circadian timing. Increasing evidence also implicates clock gene activity in the development of mood disorders. In particular, variation in the PER3 clock gene has been shown to influence diurnal preference and sleep homeostasis. However, there is not currently a clear association between PER3 polymorphisms and mood. This is possibly because the PER3 gene has been shown to influence homeostatic sleep drive, rather than circadian timing, and the PER3 gene may be behaviorally relevant only under chronic sleep loss conditions. Methods: To test the association between PER3 allele status and impaired mood, a total of 205 healthy women were genotyped for PER3 allele status and responded to previously-validated psychological questionnaires surveying self-reported sleep habits (MEQ, PSQI) and mood. Our mood measures included two measures of short-term, transient mood (state anxiety and mood disturbance) and two measures of longer term, ongoing mood (trait anxiety and depressive symptomology). Results: The PER3 genotype distribution was 88 (42.9%) for PER3(4/4), 98 (47.8%) for PER3(4/5), and 19 (9.3%) for PER3(5/5). Our sleep duration x genotype interaction analyses showed that, relative to longer allele carriers, PER3(4/4) genotypes were at greater risk for transient psychological effects (mood and state anxiety) when they reported reduced sleep durations. Conclusion: Sleep duration plays a critical role in understanding the extent to which PER3 allele status relates to mood states.